The Influence of Organizational Justice, and Teamwork towards the Employee Performance with Intrinsic Motivation as an Intervening Variable - Dewi, Santi Riana; Gentari, Rt. Erlina; Soeumaro; Marshilfi, Ega (International Journal of Science and Society, 2024)
Previous research has discussed a lot about the effect of organizational justice on performance. However, there are still inconsistencies and substantial differences between constructions. For this reason, this research goals to determine the impact of organizational justice and teamwork on employee performance with intrinsic motivation as an intermediary variable. This research was conducted at an agrochemical company in Merak, Banten, with a total of 98 respondents. This type of research is explanatory research in which the relationship between variables is explained by testing the hypothesis. Data from the questionnaires collected were then analyzed using SmartPLS 4 software. The results of the analysis showed that (1) organizational justice has a positive and significant impact on performance, (2) teamwork has a positive and significant impact on performance, (3) intrinsic motivation has a positive and significant impact on performance, (4) organizational justice has no significant impact on intrinsic motivation, (5) teamwork has a positive and significant effect on intrinsic motivation, (6) intrinsic motivation positively and significantly mediates teamwork and performance, (7) intrinsic motivation does not significantly mediate organizational justice and performance. The results of this study can be implemented by organizations to focus more on developing variables that have a significant impact on employee performance.